Five-repetition sit-to-stand test validation in adolescents and adults with intellectual disabilities - Claudio Farías-Valenzuela; Catalina Shepherd-Shepherd; Paloma Ferrero-Hernández; Guillermo F. López-Sánchez; Sebastián Espoz-Lazo; Cristian Cofre-Bolados; Pablo del Val-Martín; Eduardo R. de Victo; Gerson Ferrari (Scientific Reports, 2024)
Abstract This study aims to validate the five repetition sit to stand test (5R-STS) test as a measure of strength and functionality in adolescents and adults with intellectual disabilities (ID). The sample was made up of 159 subjects with ID (85 adolescents and 74 adults) of both sexes, with average age of 18.36 (5.26) years, belonging to four special educational centers from Santiago, Chile. Absolute (AHGS) and relative (RHGS) handgrip strength and countermovement jump (CMJ) were considered as muscle strength evaluation tests. The timed up and go (TUG) and agility test 4 × 10 m were considered as functional tests. Spearman and intraclass correlations, as well as Bland-Altman plots were used to establish the respective correlations. The average values obtained in the 5R-STS test (s) in adolescents were 6.55 and 7.24, while in adults they were 6.82 and 7.17 for men and women, respectively. Significant correlations (p = < 0.05) are established between the 5R-STS test with AHGS (r= -0.48) and RHGS (r= -0.54), CMJ (-0.53), 4 × 10 m test (-0.50) and TUG (-0.49), as well as in the analysis of agreement between 5R-STS and the TUG (ICC = 0.74) and agility 4 × 10 m (ICC = 0.61) tests, both in adolescents and adults of both sexes. The 5R-STS test is a valid, simple and safe tool to evaluate general and lower extremity muscle strength. Its use is suggested as a simple measure for monitoring functional capacity by professionals in educational and health contexts for the adolescent and adult population with ID.